Illness-associated muscle weakness in dystroglycanopathies. (5th December 2017) - Carlson, Courtney R.; McGaughey, Steven D.; Eskuri, Jamie M.; Stephan, Carrie M.; Zimmerman, M. Bridget; Mathews, Katherine D.
Abstract : Objective: To describe the phenomenon of acute illness-associated weakness (AIAW) in patients with dystroglycanopathy (DG), determine the frequency of this phenomenon in DGs, and compare it to the frequency in Duchenne-Becker muscular dystrophy (DBMD). Methods: Patients enrolled in a DG natural history study provided medical history, including major illnesses or hospitalizations, at enrollment and annually. We noted a recurring syndrome of profound transient weakness in the setting of febrile illness. To determine the frequency of this phenomenon in the DG cohort and compare it to a cohort with another membrane-related muscular dystrophy, DBMD, we surveyed patients (e-survey tool), collecting demographics and information about episodes of sudden progression of weakness and events surrounding the episodes. Results: Surveys were completed by 52 (56.6%) patients with DG and 51 (27.3%) patients with DBMD. AIAW was reported in 12 (23%) patients with DG and 2 (4%) patients with DBMD (odds ratio 7.35; 95% confidence interval 1.55, 34.77; p = 0.005). Altogether (history or survey), 21 patients with DG, with mutations in FKRP, FKTN, POMT1, POMT2, or POMGNT1, reported AIAW. These events typically occurred in children <7 years old, and the preceding illness usually included respiratory symptoms. In 10 (47.6%) patients with DG, AIAW preceded the diagnosis of muscular dystrophy. Conclusions: People with DG, across genotypes, can experience acute, transient weakness associated with a febrile illness, a phenomenon that rarely occurs in DBMD. The physiologic basis of this phenomenon is unknown. Clinicaltrials.gov identifier: NCT00313677.